STATE AND PROSPECTS OF SHIPBUILDING IN CHINA - Галай, Анна; Бондаренко, Микола (SWorldJournal, 2025)
China State Shipbuilding Corporation (CSSC) is one of the largest shipbuilding companies in the world. This industry promotes technological innovation by developing automation, green energy, and materials science, which has broad implications for other se